2017
DOI: 10.3390/ijms18091983
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Glucuronidation of Wushanicaritin by Liver Microsomes, Intestine Microsomes and Expressed Human UDP-Glucuronosyltransferase Enzymes

Abstract: Wushanicaritin, a natural polyphenol compound, exerts many biological activities. This study aimed to characterize wushanicaritin glucuronidation by pooled human liver microsomes (HLM), human intestine microsomes and individual uridine diphosphate-glucuronosyltransferase (UGT) enzyme. Glucuronidation rates were determined by incubating wushanicaritin with uridine diphosphoglucuronic acid-supplemented microsomes. Kinetic parameters were derived by appropriate model fitting. Reaction phenotyping, the relative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…D) both followed classical Michaelis–Menten equation. The K m values were simimlar with previous study , while the V max and CL int values showed significant differences ( P < 0.05) by UGT1A1 and HeLa1A1 cell lysate (Table ). Taken together, these results indicated that the engineered HeLa1A1 cells significantly expressed active UGT1A1 protein and could functionally catalyze the glucuronidation reaction.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…D) both followed classical Michaelis–Menten equation. The K m values were simimlar with previous study , while the V max and CL int values showed significant differences ( P < 0.05) by UGT1A1 and HeLa1A1 cell lysate (Table ). Taken together, these results indicated that the engineered HeLa1A1 cells significantly expressed active UGT1A1 protein and could functionally catalyze the glucuronidation reaction.…”
Section: Resultssupporting
confidence: 83%
“…Glucuronidation activities of BDMC by expressed UGT1A1 and the HeLa1A1 cell lysate were measured following our published procedures . In brief, the incubation system (200 μL) contained recombinant UGT1A1 (1.0 mg/mL) or HeLa1A1 cell lysate (9.2 mg/mL), MgCl 2 (4 mM), alamethicin (20 μg/mL), and BDMC in 50 mM Tris–HCl buffer (pH = 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned, paclitaxel was regarded as the most widely used probe substrate for CYP2C8 (Xu et al, 2018), whereas β-estradiol and propofol were recognized as the A c c e p t e d M a n u s c r i p t probe substrate for UGT1A1 and 1A3, respectively (Hong et al, 2017). As shown in Figure S4A, a significant correlation was obtained between CA-mono-oxidation and paclitaxel-6-hydroxylation (r = 0.921, p = 0.001) in a panel of HLMs (n = 9).…”
Section: Activity Correlation Analysesmentioning
confidence: 99%
“…In addition, the CL int values for the metabolic activities of PI-103 by HLM and each animal liver microsomes were used as the evaluation parameters to estimate species diversity as published previously. 20…”
Section: Species Difference Analysesmentioning
confidence: 99%